Synthesis and swelling behaviour of bentonite based superabsorbent polymer composite - Nur Sakinah, Abd Aziz (2012)
This study, is about synthesis and swelling behavior of bentonite based superabsorbent polymer(SAP)camposite.The main objective of this research is to study the optimum condition of producing bentonite based SAP by determine the effect of amount of initiator, cross-linker,and filler content towards water absorbency of the SAP. Superabsorbent polymer composite was synthesis by solution polymerization reaction of bentonite micro powder into monomer Acrylic acid (AA) using ammonium persulfate (APS) as initiator and N,N'-metylene bisacrylamide(MBA)as cross-linker in aqueous solution.The superabsorbent polymer was characterized by using Fourier Transform Infrared(FTIR)and Thermogravimetric Analysis (TGA). The water absorbency test for the SAP also performed.The result showed,optimum content to produce SAP were at 30 % initiator,10 % cross-linker and 20 % filler with water absorbency of 573.3g/g,457.3g/g and 485.4g/g in distilled water respectively.